EKSPLORASI NILAI KARAKTER DALAM FILM ANIMASI LORONG WAKTU SEBAGAI MEDIA PEMBELAJARAN DRAMA DI KELAS IV SEKOLAH DASAR - Putri Hapsari Ayuningtyas (Jurnal Pesastra (Pendidikan Bahasa dan Sastra), 2025)
This research investigates the character values found in the animated film Lorong Waktu and the film’s possible use in fourth-grade elementary school drama lessons. Applying qualitative content analysis on the selected episodes: Rantang Amanah, Terima Kasih Guru, Tolong Menolong, Koruptor, Malas Belajar, and Ngeprank, I found ten important character values: religiosity, honesty, discipline, hard work, independence, curiosity, love of reading, caring for the environment, social care, and responsibility. Among these, religiosity and responsibility are predominant. Because Lorong Waktu conveys important moral messages, the film is suitable for drama lessons. As drama activities, Ayo Bermain Peran and Ayo Mengamati can help students attitudinally and morally in a more integrated way. In conclusion, this research verifies the use of animated films in strengthening character education to other elementary school subjects.